The era of artificial intelligence–based individualized telemedicine is coming. Issue 11 (18th June 2020) - Jheng, Ying-Chun; Kao, Chung-Lan; Yarmishyn, Aliaksandr A.; Chou, Yu-Bai; Hsu, Chih-Chien; Lin, Tai-Chi; Hu, Hou-Kai; Ho, Ta-Kai; Chen, Po-Yin; Kao, Zih-Kai; Chen, Shih-Jen; Hwang, De-Kuang
Abstract : Artificial intelligence (AI), Internet of Things (IoT), and telemedicine are deeply involved in our daily life and have also been extensively applied in the medical field, especially in ophthalmology. Clinical ophthalmologists are required to perform a vast array of image exams and analyze images containing complicated information, which allows them to diagnose the disease type and grade, make a decision on remedy, and predict treatment outcomes. AI has a great potential to assist ophthalmologists in their daily routine of image analysis and relieve their work burden. However, in spite of these prospects, the application of AI may also be controversial and associated with several legal, ethical, and sociological concerns. In spite of these issues, AI has indeed become an irresistible trend and is widely used by medical specialists in their daily routines in what we can call now, the era of AI. This review will encompass those issues and focus on recent research on the AI application in ophthalmology and telemedicine.